Morphometrics of the Blue Crab Callinectes sapidus Rathbun, 1896 in a Northern Adriatic Saline Marsh Under Environmental Stress - Neven Iveša; Paolo Paliaga; Matej Čief; Petra Burić; Valentina Pitacco; Moira Buršić (Applied Sciences, 2025)
The Atlantic blue crab (Callinectes sapidus) has rapidly expanded across the Mediterranean, raising concerns over its ecological and economic impacts. This study examines the morphometric characteristics and environmental influences on C. sapidus populations in the Palud-Palù swamp (western Istrian coast) from 2022 to 2024. A total of 203 specimens were analyzed for carapace width, length, depth, and body mass, alongside monthly measurements of temperature, salinity, oxygen saturation, and pH. Statistical analyses (t-tests, ANOVA, PCA, and RDA) revealed pronounced sexual dimorphism, with males consistently larger than females. Interannual differences in size distribution showed larger individuals in 2022, followed by a decline in 2023 and 2024, likely due to environmental stressors (e.g., salinity, temperature, hypoxia) and increased anthropogenic pressures (e.g., trapping and illegal harvesting). RDA identified temperature, oxygen saturation, and pH as key abiotic drivers of morphometric variation. These findings suggest that while C. sapidus demonstrates physiological plasticity, enabling its persistence in estuarine environments, its growth and invasive potential may be constrained under extreme or suboptimal local conditions. This study highlights the importance of long-term monitoring and integrated management to mitigate ecological disruption in sensitive coastal ecosystems.